Model Penerimaan Aplikasi BRISPOT BRI Unit Dengan Pendekatan Technology Acceptance Model (TAM) - Bona Tua, Marco; Hartoyo; Yuliati, Lilik Noor (School of Business, Bogor Agricultural University (SB-IPB), 2022)
BRISPOT is BRI's innovative step in Financial Technology (Fintech) services to accelerate the micro credit process, be more efficient, paperless and digital-based. This study analyzes the acceptance of the use of the BRISPOT application in BRI Kanca Karawang. One of the models used in analyzing technology acceptance is the Technology Acceptance Model (TAM). This research was conducted from December 2019 to February 2020. The population in this study amounted to 124 respondents with the criteria for respondents in this study were marketers who had used BRISPOT. Methods and data analysis using PLS-SEM. The results showed that perceived resources and self efficacy had a significant effect on perceived ease of use, perceived ease of use had a significant effect on perceived usefulness, perceived usefulness had a significant effect on attitude toward using, and attitude toward using had a significant effect on actual use of BRISPOT. The managerial implication in this research is that management can improve the upload feature of business photos and debtors' collateral and add the BRISPOT employee care feature to the application so that respondents can immediately ask questions and get solutions to problems with features that are experiencing interference. Keywords: BRISPOT, IPMA, PLS, TAM, sales marketing